A thermo-mechanical model for pile-soil interface behavior. Issue 7 (October 2021) - Wang, Xiaoqiang; Wang, Jingkai; Zhang, Zhichao
Abstract: This study proposes a constitutive model of the pile-soil interface based on a thermodynamic approach. Firstly, the thermo-elastic coupled nonlinear hyperelastic relation of the pile-soil interface is derived by defining the interface potential energy function of the pile-soil interface subjected to normal and tangential forces. The plastic interface constitutive relations are then developed using non-equilibrium thermodynamics, based on the energy dissipations caused by the pile-soil interface's shear-induced slipping behavior. The stress- and temperature-dependent pile-soil interface behavior is described using the concept of interface density and the normal elastic thermal expansion coefficient.